Carbon and Nitrogen Mineralization in Soil Amended with Value-added Manures and Fertilizers under Varying Temperature and Soil Moisture Regimes - D.R. Biswas, B.B. Basak and (Journal of the Indian Society of Soil Science, 2014)
The main aim of this study was to quantify the C and N mineralization rates in soil from organic and inorganic fertilizers as affected by temperature and moisture regimes. Laboratory incubation experiment was carried out with eight treatments consisting of combinations of value-added organic manures namely, vermicompost, NADEP compost, FYM and inorganic fertilizers. Soil (40 g) was mixed thoroughly with required quantities of organic manures and chemical fertilizers and placed in 500 mL hermetically sealed flasks and incubated at two temperatures viz., 20 and 35 oC and two soil moisture regimes viz., 0.33 bar (field capacity) and 1.0 bar for 7, 15, 30, 60 and 90 days. Destructive samplings were done and C mineralization and mineral N were determined at each interval. Data emanated were fitted to first-order exponential equation to predict the potential mineralizable C (CO) and N (NO) as well as mineralization constants (kC and kN). Results indicated that highest values of C mineralization and mineral N were associated with treatment containing value-added organic manures in combination with fertilizers. Across the incubation periods and treatments, around 15.4% increase in C mineralization was observed due to increase in temperature from 20 to 35 oC while 73.3% increase was observed as the soil moisture regime shifted from 1.0 bar to field capacity. Similarly, around 5.7% increase in mineral N was recorded due to increase in temperature from 20 to 35 oC while 10.2% increase was observed as the soil moisture regime shifted from 1.0 bar to field capacity. Data on C and N mineralization were well fitted to exponential equation as evidenced from their correlation coefficients (R2) values. Potential mineralizable C and N as well as mineralization constants were significantly influenced by the application of organic manures in combination with fertilizers.